2005
DOI: 10.1073/pnas.0409186102
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of expression and regulatory divergences after yeast gene duplication

Abstract: Although gene duplication is widely believed to be the major source of genetic novelty, how the expression or regulatory network of duplicate genes evolves remains poorly understood. In this article, we propose an additive expression distance between duplicate genes, so that the evolutionary rate of expression divergence after gene duplication can be estimated through phylogenomic analysis. We have analyzed yeast genome sequences, microarrays, and transcriptional regulatory networks, showing a >10-fold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 34 publications
14
138
1
Order By: Relevance
“…Previous studies comparing gene expression levels of duplicate genes revealed that expression divergence between copies occurs rapidly (31)(32)(33)(34)(35)(36)(37)(38) and can be asymmetric (32,35,38). However, our analysis is unique in that it uses expression data and phylogenetic relationships among genes to explicitly classify the evolutionary processes underlying the retention of duplicates on a genome-wide scale.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing gene expression levels of duplicate genes revealed that expression divergence between copies occurs rapidly (31)(32)(33)(34)(35)(36)(37)(38) and can be asymmetric (32,35,38). However, our analysis is unique in that it uses expression data and phylogenetic relationships among genes to explicitly classify the evolutionary processes underlying the retention of duplicates on a genome-wide scale.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, diverse authors have proposed that while paralogues may retain similar functionality, gene expression rapidly diverges immediately after duplication events (Gu et al, , 2002Li et al, 2005), implying that alterations in gene expression precede potential changes in function. Furthermore, it has been postulated that paralogous genes which diverge in function contribute to evolutionary innovation at a biochemical level (Evangelisti & Wagner, 2004;Gu et al, 2005Gu et al, , 2002Zhang et al, 1998). In order to corroborate these observations, we analysed the metabolic divergence of paralogous genes.…”
Section: Databasesmentioning
confidence: 90%
“…As an initial effort to spark interests in exploring these important issues and also motivated by discoveries that duplicated genes can develop divergent regulation and expression pattern, [18][19][20] we have recently characterized the profiles of histone modifications in the human segmental duplications. 21 We found that the two regions www.landesbioscience.com Epigenetics 251…”
mentioning
confidence: 99%